Composite copper powder and preparation method and application thereof
By combining diverse sulfur compounds with the surface of copper particles to form a strong collaboration cooperation, the problem of low copper electrical and oxidation is solved, which significantly improves the thermal stability and antioxidant of composite copper powder. It is suitable for solar cells and other fields High -efficiency conductive materials.
Patent Information
- Application Number
- CN202310911969.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-01-28
AI Technical Summary
In the prior art, copper has low conductivity and is prone to oxidation, resulting in a sharp increase in resistivity when used at high temperatures, making it difficult to meet the cost reduction and widespread popularization needs in fields such as solar cells.
The combination of multiple sulfur compounds with the surface of copper particles is used to form a strong collaboration with the surface of the five -dollar ring, six -yuan ring, seven -dollar ring or an eight -yuan ring structure with nearly plane. Essence
It significantly improves the starting temperature of the composite copper powder, makes the starting temperature of its heat oxidation exceeding 250 ° C, and maintains good antioxidant performance at high temperature, suitable for large -scale production.
Smart Images

Figure CN119368728A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive pastes, and in particular relates to a composite copper powder and a preparation method and application thereof. Background Art
[0002] Currently, electronic pastes with silver or silver-clad copper as the conductive phase have been widely used in printed circuit boards, solar cells and other fields. Especially in recent years, with the rapid expansion of solar cell companies, the demand for silver will increase sharply. However, due to the high price of silver and the existence of migration phenomenon, this will greatly hinder the cost reduction of solar cells and is not conducive to the widespread popularization of solar cells.
[0003] Copper has a slightly lower conductivity than silver and is a good alternative to silver. However, copper is more easily oxidized than silver, which has become a bottleneck in the development of electronic copper paste. In the prior art, the oxidation problem of copper is usually solved by modifying its surface with organic matter, such as benzotriazole, fatty acid, fatty amine, etc. However, at higher temperatures, the copper surface modified with these organic matter will still be oxidized by oxygen, which leads to a sharp increase in resistivity.
[0004] In the prior art, the technology of using mercaptan as copper surface modification organic matter has gradually developed. Due to the strong complexation between sulfur and copper, the mercaptan compound has a good antioxidant effect. However, since the mercaptan (such as alkyl mercaptan) in actual use usually has a low flash point and high volatility, its special odor has an adverse effect on the operator's body and mind, which is not conducive to large-scale production. At the same time, although the strong complexation between sulfur and copper improves the antioxidant property, its antioxidant property still does not meet the strict use requirements, and there is still a lot of room for improvement. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the purpose of the present invention is to provide a composite copper powder and a preparation method and application thereof. The present invention improves the thermal stability and oxidation resistance of the composite copper powder, thereby increasing the oxidation starting temperature of the composite copper powder, so that the thermal oxidation starting temperature of the composite copper powder is greater than 250°C.
[0006] In one aspect of the present invention, the present invention provides a composite copper powder. According to an embodiment of the present invention, the composite copper powder comprises:
[0007] Copper particles; and
[0008] A polysulfur compound attached to the surface of the copper particles, wherein the polysulfur compound is selected from at least one of the compounds represented by formula I, formula II, formula III and formula IV;
[0009]
[0010] wherein A1, A2, A3, A4, A5 are each independently selected from S, C=S, C or C-SH groups, and at least two of A1, A2, A3, A4 and A5 are each independently selected from S, C=S or C-SH groups; X1, X2, X3, X4, X5, X6 are each independently selected from S, C=S, C or C-SH groups, and at least two of X1, X2, X3, X4, X5 and X6 are each independently selected from S, C=S or C-SH groups; B1, B2, B3, B 4. B5, B6, and B7 are each independently selected from S, C=S, C, or C-SH groups, and at least two of B1, B2, B3, B4, B5, B6, and B7 are each independently selected from S, C=S, or C-SH groups; L1, L2, L3, L4, L5, L6, L7, and L8 are each independently selected from S, C=S, C, or C-SH groups, and at least two of L1, L2, L3, L4, L5, L6, L7, and L8 are each independently selected from S, C=S, or C-SH groups;
[0011] A1, A2, A3, A4, A5 may be optionally and independently substituted by R1, X1, X2, X3, X4, X5, X6 may be optionally and independently substituted by R2, B1, B2, B3, B4, B5, B6, B7 may be optionally and independently substituted by R3, L1, L2, L3, L4, L5, L6, L7, L8 may be optionally and independently substituted by R4, and R1, R2, R3, R4 are each independently selected from H, substituted or unsubstituted alkyl having 1 to 25 carbon atoms, substituted or unsubstituted alkenyl having 1 to 20 carbon atoms, substituted or unsubstituted alkynyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted aryl having 6 to 20 carbon atoms, and substituted or unsubstituted aralkyl having 7 to 20 carbon atoms.
[0012] According to the composite copper powder of the embodiment of the present invention, the polysulfur compound has a nearly planar five-membered ring, six-membered ring, seven-membered ring or eight-membered ring as the main structure, and multiple sulfur atoms on or adjacent to the five-membered ring, six-membered ring, seven-membered ring or eight-membered ring are adsorbed on the copper surface, so that the copper particles can better block the penetration of water and oxygen. Moreover, most of the sulfur and copper are close to each other in space, and it is easy to produce complexation. At the same time, the matching atomic distance also makes the interface energy between copper and sulfur lower, which improves the thermal stability of the composite copper powder, thereby increasing the oxidation starting temperature of the composite copper powder, and making the thermal oxidation starting temperature of the composite copper powder>250°C.
[0013] In addition, the composite copper powder according to the above embodiment of the present invention may also have the following additional technical features:
[0014] In some embodiments of the present invention, R1, R2, R3, and R4 are each independently selected from a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 1 to 15 carbon atoms, a substituted or unsubstituted alkynyl group having 1 to 10 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 15 carbon atoms, a substituted or unsubstituted aryl group having 6 to 15 carbon atoms, and a substituted or unsubstituted aralkyl group having 7 to 15 carbon atoms.
[0015] In some embodiments of the present invention, the substituents on R1, R2, R3, and R4 are each independently selected from H, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 1 to 10 carbon atoms, an alkynyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms.
[0016] In some embodiments of the present invention, the polysulfur compound is selected from at least one of the following compounds, wherein -C4H9, -C 12 H 25 , -C 15 H 31 , -C 19 H 39 All are straight chain alkyl groups:
[0017]
[0018] In some embodiments of the present invention, based on the total mass of the composite copper powder being 100%, the mass of the polysulfide compound attached to the surface of the copper particles is 0.01-0.5%.
[0019] In some embodiments of the present invention, the burn-out rate of the composite copper powder when burned to 700° C. is 0.01-0.5%.
[0020] In some embodiments of the present invention, the thermal oxidation starting temperature of the composite copper powder is greater than 250°C.
[0021] In some embodiments of the present invention, the copper particles are flaky copper particles and / or spherical copper particles, the D50 particle size of the flaky copper particles is 1 to 50 μm; the D50 particle size of the spherical copper particles is 10 to 1000 nm.
[0022] In another aspect of the present invention, the present invention provides a method for preparing the above-mentioned composite copper powder. According to an embodiment of the present invention, the method comprises:
[0023] (1) pre-treating the copper particles to remove foreign matter on the surface of the copper particles;
[0024] (2) preparing a polysulfide compound solution;
[0025] (3) mixing the pretreated copper particles with the polysulfide compound solution, stirring and / or ultrasonically treating, washing, and drying to obtain composite copper powder.
[0026] According to the method for preparing the above-mentioned composite copper powder in an embodiment of the present invention, the polysulfur compound has a nearly planar five-membered ring, six-membered ring, seven-membered ring or eight-membered ring as the main structure, and multiple sulfur atoms on or adjacent to the five-membered ring, six-membered ring, seven-membered ring, eight-membered ring are adsorbed on the copper surface, so that the copper particles can better block the penetration of water and oxygen. And most of the sulfur and copper are close to each other in space, and it is easy to produce complexation. At the same time, the matching atomic spacing also makes the interface energy between copper and sulfur lower, which improves the thermal stability of the composite copper powder, thereby increasing the oxidation starting temperature of the composite copper powder, so that the thermal oxidation starting temperature of the composite copper powder is greater than 250°C. And the preparation method is simple and easy to implement, and the solvents and chemicals used are odorless, low in toxicity, and conducive to large-scale production.
[0027] In addition, the method for preparing composite copper powder according to the above embodiment of the present invention may also have the following additional technical features:
[0028] In some embodiments of the present invention, in step (1), the copper particles are pretreated with an acid solution;
[0029] And / or, in step (2), the mass concentration of the polysulfide compound solution is 1 to 20%;
[0030] And / or, in step (3), mixing, stirring or ultrasonic treatment is carried out at 20 to 80° C., and the stirring or ultrasonic treatment time is 30 to 600 min.
[0031] In the third aspect of the present invention, the present invention provides a conductive paste. According to an embodiment of the present invention, the conductive paste includes the composite copper powder described in the above embodiment or the composite copper powder prepared by the method described in the above embodiment. Thus, the conductive paste formed has excellent oxidation resistance and thermal stability, and the electrode grid line formed after the conductive paste is cured has excellent oxidation resistance and thermal stability.
[0032] In a fourth aspect of the present invention, the present invention provides an electrode. According to an embodiment of the present invention, the electrode comprises the conductive paste of the above embodiment, so that the electrode has excellent oxidation resistance and thermal stability.
[0033] In a fifth aspect of the present invention, the present invention provides a solar cell. According to an embodiment of the present invention, the solar cell has the electrode of the above embodiment. Thus, the solar cell has all the advantages of the electrode of the above embodiment.
[0034] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0036] Figure 1 This is a thermogravimetric curve of the composite copper particles prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0037] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0038] In one aspect of the present invention, the present invention provides a composite copper powder. According to an embodiment of the present invention, the composite copper powder comprises: copper particles; and a polysulfide compound attached to the surface of the copper particles, wherein the polysulfide compound is selected from at least one of the compounds represented by formula I, formula II, formula III and formula IV;
[0039]
[0040] wherein A1, A2, A3, A4, A5 are each independently selected from S, C=S, C or C-SH groups, and at least two of A1, A2, A3, A4 and A5 are each independently selected from S, C=S or C-SH groups; X1, X2, X3, X4, X5, X6 are each independently selected from S, C=S, C or C-SH groups, and at least two of X1, X2, X3, X4, X5 and X6 are each independently selected from S, C=S or C-SH groups; B1, B2, B3, B 4. B5, B6, and B7 are each independently selected from S, C=S, C, or C-SH groups, and at least two of B1, B2, B3, B4, B5, B6, and B7 are each independently selected from S, C=S, or C-SH groups; L1, L2, L3, L4, L5, L6, L7, and L8 are each independently selected from S, C=S, C, or C-SH groups, and at least two of L1, L2, L3, L4, L5, L6, L7, and L8 are each independently selected from S, C=S, or C-SH groups;
[0041] A1, A2, A3, A4, A5 may be optionally and independently substituted by R1, i.e. when A1, A2, A3, A4, A5 do not contain H, for example when A1, A2, A3, A4, A5 are each independently selected from C=S or S, then A1, A2, A3, A4, A5 do not contain H and are not substituted. When A1, A2, A3, A4, A5 contain H, the H on A1, A2, A3, A4, A5 may be substituted by R1 or may not be substituted; when multiple H on A1, A2, A3, A4, A5 are substituted by R1, the multiple substituents R1 may be the same or different, and the multiple substituents R1 are each independently selected from H, substituted or unsubstituted alkyl having 1 to 25 carbon atoms, substituted or unsubstituted alkenyl having 1 to 20 carbon atoms, substituted or unsubstituted alkynyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted aryl having 6 to 20 carbon atoms, and substituted or unsubstituted aralkyl having 7 to 20 carbon atoms.
[0042] X1, X2, X3, X4, X5, and X6 may be optionally and independently substituted by R2, i.e., when X1, X2, X3, X4, X5, and X6 do not contain H, for example, when X1, X2, X3, X4, X5, and X6 are each independently selected from C=S or S, then X1, X2, X3, X4, X5, and X6 do not contain H and are not substituted. When X1, X2, X3, X4, X5, and X6 contain H, the H on X1, X2, X3, X4, X5, and X6 may be substituted by R2 or may not be substituted; when multiple H on X1, X2, X3, X4, X5, and X6 are substituted by R2, the multiple substituents R2 may be the same or different, and the multiple substituents R2 are each independently selected from H, substituted or unsubstituted alkyl having 1 to 25 carbon atoms, substituted or unsubstituted alkenyl having 1 to 20 carbon atoms, substituted or unsubstituted alkynyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted aryl having 6 to 20 carbon atoms, and substituted or unsubstituted aralkyl having 7 to 20 carbon atoms.
[0043] B1, B2, B3, B4, B5, B6, B7 may be optionally and independently substituted by R3, i.e. when B1, B2, B3, B4, B5, B6, B7 do not contain H, for example when B1, B2, B3, B4, B5, B6, B7 are each independently selected from C=S or S, then B1, B2, B3, B4, B5, B6, B7 do not contain H and are not substituted. When B1, B2, B3, B4, B5, B6, and B7 contain H, the H on B1, B2, B3, B4, B5, B6, and B7 may be substituted by R3 or may not be substituted; when multiple H on B1, B2, B3, B4, B5, B6, and B7 are substituted by R3, the multiple substituents R3 may be the same or different, and the multiple substituents R3 are each independently selected from H, substituted or unsubstituted alkyl having 1 to 25 carbon atoms, substituted or unsubstituted alkenyl having 1 to 20 carbon atoms, substituted or unsubstituted alkynyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted aryl having 6 to 20 carbon atoms, and substituted or unsubstituted aralkyl having 7 to 20 carbon atoms.
[0044] L1, L2, L3, L4, L5, L6, L7, L8 may be optionally and independently substituted by R4, i.e. when L1, L2, L3, L4, L5, L6, L7, L8 do not contain H, for example when L1, L2, L3, L4, L5, L6, L7, L8 are each independently selected from C=S or S, then L1, L2, L3, L4, L5, L6, L7, L8 do not contain H and are not substituted. When L1, L2, L3, L4, L5, L6, L7, and L8 contain H, the H on L1, L2, L3, L4, L5, L6, L7, and L8 may be substituted by R4 or may not be substituted; when multiple H on L1, L2, L3, L4, L5, L6, L7, and L8 are substituted by R4, the multiple substituents R4 may be the same or different, and the multiple substituents R4 are each independently selected from H, substituted or unsubstituted alkyl having 1 to 25 carbon atoms, substituted or unsubstituted alkenyl having 1 to 20 carbon atoms, substituted or unsubstituted alkynyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted aryl having 6 to 20 carbon atoms, and substituted or unsubstituted aralkyl having 7 to 20 carbon atoms.
[0045] According to the composite copper powder of the embodiment of the present invention, the polysulfur compound has a nearly planar five-membered ring, six-membered ring, seven-membered ring or eight-membered ring as the main structure, and multiple sulfur atoms on or adjacent to the five-membered ring, six-membered ring, seven-membered ring or eight-membered ring are adsorbed on the copper surface, so that the copper particles can better block the penetration of water and oxygen. Moreover, most of the sulfur and copper are close to each other in space, and it is easy to produce complexation. At the same time, the matching atomic distance also makes the interface energy between copper and sulfur lower, which improves the thermal stability of the composite copper powder, thereby increasing the oxidation starting temperature of the composite copper powder, and making the thermal oxidation starting temperature of the composite copper powder>250°C.
[0046] The principle by which the composite copper powder proposed in the present invention can achieve the above beneficial effects is described in detail below:
[0047] Compared with aliphatic chain alkyl mercaptan, the polysulfur compound used in the present invention is based on a nearly planar five-membered ring, six-membered ring, seven-membered ring or eight-membered ring as the main structure, and at least two sulfur atoms are included on the five-membered ring, six-membered ring, seven-membered ring, eight-membered ring or in an atom adjacent to the five-membered ring, six-membered ring, seven-membered ring, eight-membered ring or in an atom adjacent to the five-membered ring, six-membered ring, seven-membered ring, eight-membered ring, which are different from the upright arrangement of aliphatic chain alkyl mercaptan on the copper surface (the sulfhydryl group at the hydrophilic end is adsorbed on the copper surface, and the alkyl group at the hydrophobic end is facing away from the copper surface), the five-membered ring, six-membered ring, seven-membered ring, eight-membered ring are close to the copper surface in a nearly planar manner, and a plurality of sulfur atoms on or adjacent to the five-membered ring, six-membered ring, seven-membered ring, eight-membered ring are adsorbed on the copper surface, which can better block the penetration of water and oxygen compared with aliphatic chain alkyl mercaptan. Specifically, a plurality of sulfur atoms on or adjacent to the five-membered ring, six-membered ring, seven-membered ring, eight-membered ring all have lone pairs of electrons, and copper has an empty orbit of d, so a coordination bond can be formed between the sulfur atom and the copper, so that the polysulfur compound is stably attached to the copper surface.
[0048] Furthermore, since the carbon-sulfur bond length is about 0.18nm and the lattice constant of copper is about 0.36nm, which is twice the carbon-sulfur bond length, most of the sulfur and copper are close to each other in space, and complexation can be easily produced. At the same time, the matching atomic spacing also makes the interface energy between copper and sulfur lower, thereby improving the thermal stability of the modified copper particles, thereby increasing the oxidation starting temperature and making the thermal oxidation starting temperature of the composite copper powder greater than 250°C.
[0049] Compared with monovalent thiol compounds, the polyvalent sulfur compounds used in the present invention have stronger complexation with copper, that is, the polyvalent sulfur compounds have stronger binding force with copper. Under the action of the outside world (heat, acid and alkali, etc.), the monovalent thiol is easily desorbed, resulting in a decrease in antioxidant performance, while the multi-point complexation method produces a strong synergistic effect. Even if one point is desorbed, the complexation at other positions can still effectively ensure that the polyvalent sulfur compound is adsorbed on the copper surface, thereby improving the antioxidant performance. Therefore, it can be ensured that the composite copper powder is not oxidized at a higher temperature, and the oxidation starting temperature of the composite copper powder is increased, so that the thermal oxidation starting temperature of the composite copper powder is greater than 250°C.
[0050] As some specific examples, R1, R2, R3, and R4 are each independently selected from substituted or unsubstituted alkyl groups with 1 to 20 carbon atoms, substituted or unsubstituted alkenyl groups with 1 to 15 carbon atoms, substituted or unsubstituted alkynyl groups with 1 to 10 carbon atoms, substituted or unsubstituted cycloalkyl groups with 3 to 15 carbon atoms, substituted or unsubstituted aryl groups with 6 to 15 carbon atoms, and substituted or unsubstituted aralkyl groups with 6 to 15 carbon atoms. As some specific examples, the substituents on R1, R2, R3, and R4 are each independently selected from H, alkyl groups with 1 to 10 carbon atoms, alkenyl groups with 1 to 10 carbon atoms, alkynyl groups with 1 to 10 carbon atoms, cycloalkyl groups with 3 to 10 carbon atoms, and aryl groups with 6 to 10 carbon atoms. The above-mentioned polysulfur compounds further improve the thermal stability of the composite copper powder, thereby increasing the oxidation starting temperature of the composite copper powder.
[0051] Preferably, R1, R2, R3, and R4 are each independently selected from an unsubstituted alkyl group having 1 to 20 carbon atoms, an unsubstituted alkenyl group having 1 to 15 carbon atoms, an unsubstituted alkynyl group having 1 to 10 carbon atoms, an unsubstituted cycloalkyl group having 3 to 15 carbon atoms, an unsubstituted aryl group having 6 to 15 carbon atoms, and an unsubstituted aralkyl group having 6 to 15 carbon atoms. The above-mentioned polysulfur compounds further improve the thermal stability of the composite copper powder, thereby increasing the oxidation starting temperature of the composite copper powder.
[0052] As some specific examples, the polysulfur compound is selected from at least one of the following compounds, wherein -C4H9, -C 12 H 25 , -C 15 H 31 , -C 19 H 39 All are straight chain alkyl groups:
[0053]
[0054] The above-mentioned polysulfur compounds further improve the thermal stability of the composite copper powder, thereby increasing the oxidation starting temperature of the composite copper powder.
[0055] According to some specific embodiments of the present invention, based on the total mass of the composite copper powder being 100%, the mass of the polysulfide compound attached to the surface of the copper particles is 0.01-0.5% (for example, it can be 0.01 / 0.03 / 0.05 / 0.07 / 0.1 / 0.15 / 0.2 / 0.3 / 0.4 / 0.5%), preferably 0.05-0.2%. By limiting the mass of the polysulfide compound attached to the surface of the copper particles to the above range, it is further ensured that the polysulfide compound can effectively attach to the surface of the copper particles, effectively improving the thermal stability of the composite copper powder, thereby effectively increasing the oxidation start temperature of the composite copper powder.
[0056] According to some further specific embodiments of the present invention, the burnout rate of the composite copper powder when burned to 700°C is 0.01-0.5% (for example, it can be 0.01 / 0.03 / 0.05 / 0.07 / 0.1 / 0.15 / 0.2 / 0.3 / 0.4 / 0.5%), preferably 0.05-0.2%. The burnout rate is tested by a thermogravimetric method. Specifically, the composite copper powder is burned to 700°C in a muffle furnace under a nitrogen atmosphere, and weighed immediately after cooling. The difference in mass before and after burning is divided by the mass before burning to obtain the burnout rate.
[0057] According to some further specific embodiments of the present invention, the copper particles are flaky copper particles and / or spherical copper particles, the D50 particle size of the flaky copper particles is 1 to 50 μm, preferably 1 to 20 μm; the D50 particle size of the spherical copper particles is 10 to 1000 nm, preferably 50 to 800 nm.
[0058] In another aspect of the present invention, the present invention provides a method for preparing the above-mentioned composite copper powder. According to an embodiment of the present invention, the method comprises:
[0059] S100: Pre-treatment of copper particles
[0060] In this step, the copper particles are pretreated to remove foreign matter (such as oil stains, impurities, oxides, etc.) on the surface of the copper particles, thereby facilitating the polysulfide compounds to adhere smoothly to the surface of the copper particles.
[0061] As some specific examples, the copper particles can be pretreated with an acid solution, for example: the copper particles are cleaned with a hydrochloric acid or sulfuric acid aqueous solution with a mass fraction of 0.1 to 5%, the pickling temperature can be 20 to 50°C, the pickling time can be 30 to 90 minutes, and after pickling, deionized water is used to wash until the system is neutral, and then anhydrous ethanol is used to wash to remove excess water.
[0062] S200: Preparation of polysulfide solution
[0063] In this step, a polysulfide compound solution is prepared for later use.
[0064] As some specific examples, the mass concentration of the polysulfide compound solution can be 1-20%, for example, 1 / 2 / 4 / 6 / 8 / 10 / 12 / 14 / 16 / 18 / 20%. This can effectively ensure that when the copper particles are mixed with the polysulfide compound solution, the polysulfide compounds in the polysulfide compound solution can be orderly attached to the surface of the copper particles, ensuring that multiple sulfur atoms in the polysulfide compounds can be adsorbed on the surface of the copper particles, avoiding the disorderly attachment of the polysulfide compounds to the surface of the copper particles due to the excessively high concentration of the polysulfide compound solution, further effectively improving the thermal stability of the composite copper powder, thereby effectively increasing the oxidation starting temperature of the composite copper powder.
[0065] In addition, the type of solvent for the polysulfide compound solution is not particularly limited, and may be any volatile organic solvent such as alcohol, lipid, or ketone solvents.
[0066] S300: mixing the pretreated copper particles with the polysulfide compound solution, stirring and / or ultrasonically treating, washing, and drying
[0067] In this step, the pretreated copper particles are mixed with the polysulfide solution, stirred and / or ultrasonically treated, so that multiple sulfur atoms on or adjacent to the five-membered ring, six-membered ring, seven-membered ring, eight-membered ring in the polysulfide compound are adsorbed on the copper surface through coordination bonds, thereby adsorbing the polysulfide compound on the surface of the copper particles. Stirring and / or ultrasonic treatment has the effect of accelerating the adsorption speed and making the polysulfide compound more uniformly adsorbed on the surface of the copper particles.
[0068] Furthermore, mixing, stirring or ultrasonic treatment is performed at 20 to 80° C., and the stirring or ultrasonic treatment time is 30 to 600 minutes, thereby further ensuring that the polysulfide compound is more fully and effectively adsorbed on the surface of the copper particles.
[0069] Furthermore, the volume ratio of the copper particles to the polysulfide compound solution is 1:(1-2), which further ensures that the polysulfide compound is more fully and effectively adsorbed on the surface of the copper particles.
[0070] The copper particles are then cleaned with a solvent for 1 to 5 times, and dried in a vacuum oven at 20 to 50° C. for 2 to 6 hours to finally obtain composite copper particles.
[0071] In the third aspect of the present invention, the present invention provides a conductive paste. According to an embodiment of the present invention, the conductive paste includes the composite copper powder described in the above embodiment or the composite copper powder prepared by the method described in the above embodiment. Thus, the conductive paste formed has excellent oxidation resistance and thermal stability, and the electrode grid line formed after the conductive paste is cured has excellent oxidation resistance and thermal stability.
[0072] Specifically, the conductive paste further includes epoxy resin, solvent, dispersant, accelerator and the like.
[0073] In the embodiment of the present invention, the content of each component in the conductive paste belongs to the conventional amount in the art and will not be described in detail here.
[0074] In a fourth aspect of the present invention, the present invention provides an electrode. According to an embodiment of the present invention, the electrode comprises the conductive paste of the above embodiment, so that the electrode has excellent oxidation resistance and thermal stability.
[0075] Specifically, the electrode may be a positive electrode or a negative electrode.
[0076] In a fifth aspect of the present invention, the present invention provides a solar cell. According to an embodiment of the present invention, the solar cell has the electrode of the above embodiment. Thus, the solar cell has all the advantages of the electrode of the above embodiment.
[0077] The embodiments of the present invention are described in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and cannot be interpreted as limiting the present invention. In addition, if not explicitly stated, all reagents used in the following embodiments are commercially available, or can be synthesized according to this article or known methods, and the reaction conditions not listed are also easily available to those skilled in the art.
[0078] Example 1
[0079] Step 1: Pickling copper particles. Add 100 g of flaky copper particles with a particle size of D50 = 1 μm to 100 mL of a 0.5% sulfuric acid solution, stir at 25°C for 60 min, centrifuge and filter, pour out the supernatant, wash with 100 mL of deionized water until the supernatant is pH neutral, and wash with 100 mL of anhydrous ethanol for 3 times.
[0080] Step 2: Weigh 2.5 g of compound 1 and prepare it into a 5% ethanol solution by mass, add 50 g of copper particles after acid washing into 50 mL of the solution, stir at 40 ° C for 240 min, centrifuge and filter, wash the copper particles with anhydrous ethanol for 3 times, and bake at 50 ° C in a vacuum oven (vacuum degree ≤ -0.095 MPa) for 2 h to obtain composite copper particles.
[0081]
[0082] Example 2
[0083] Step 1: Acid-washing copper particles. Add 100 g of spherical copper particles with a particle size of D50 = 500 nm to 100 mL of 1% sulfuric acid solution, stir at 35°C for 45 min, centrifuge and filter, pour out the supernatant, wash with 100 mL of deionized water until the supernatant is pH neutral, and wash with 100 mL of anhydrous ethanol for 3 times.
[0084] Step 2: Weigh 5 g of compound 2 and prepare it into a 10% mass fraction acetone solution, add 50 g of copper particles after acid washing into 50 mL of the solution, stir at 60 ° C for 120 min, centrifuge and filter, wash the copper particles with acetone 3 times, and bake in a vacuum oven (vacuum degree ≤ -0.095 MPa) at 40 ° C for 2 h to obtain composite copper particles.
[0085]
[0086] Examples 3 to 16 and comparative examples 1 to 3 were obtained in a similar manner to Example 1, and their parameters are shown in Table 1. Other contents are the same as those of Example 1.
[0087] Table 1
[0088]
[0089]
[0090]
[0091] In order to prove that the composite copper particles modified by polysulfide compounds have excellent oxidation resistance, the TG (thermal gravimetric loss) curves of Examples 1 to 16 and Comparative Examples 1 to 3 were tested (see Figure 2). Figure 1 The TG curve was tested by a thermal analysis system (TGA / DSC) of Mettler Toledo Corporation. The test conditions were as follows: the temperature was raised from 30°C to 500°C at a rate of 10K / min in an air atmosphere. The first-order derivative of the TG curve was obtained, and the oxidation starting temperature of each composite copper particle was obtained by the tangent method, as shown in Table 1.
[0092] Table 2
[0093] Serial number Oxidation starting temperature / ℃ Serial number Oxidation starting temperature / ℃ Example 1 278 Embodiment 11 283 Example 2 257 Example 12 255 Example 3 286 Example 13 266 Example 4 305 Embodiment 14 280 Example 5 277 Embodiment 15 278 Example 6 261 Example 16 285 Example 7 311 Comparative Example 1 132 Example 8 298 Comparative Example 2 178 Example 9 270 Comparative Example 3 154 Example 10 267
[0094] It can be seen from Table 2 that the composite copper particles on the surface of the polysulfur compound-modified copper of Examples 1 to 16 of the present invention have excellent oxidation resistance. Under the same conditions, the oxidation starting temperature of Example 7 can reach 311°C, which is much higher than 178°C of Comparative Example 2; under the same conditions, the oxidation starting temperature of Example 8 can reach 298°C, which is much higher than 132°C of Comparative Example 1.
[0095] In order to further prove that the composite copper particles in the embodiments of the present invention are not oxidized before the oxidation starting temperature, Examples 1 to 16 and Comparative Examples 1 to 3 are baked in an air blast oven at 180° C. for 60 min, and their oxygen contents are detected by an oxygen, nitrogen and hydrogen combined tester (ONH836) of LECO Company of the United States. The results are shown in Table 3.
[0096] Table 3
[0097]
[0098] As can be seen from Table 3, after high-temperature baking in air, the oxygen content of the composite copper particles in Examples 1-16 only increased slightly, indicating that they were not oxidized before the oxidation starting temperature, while the oxygen content in the copper particles in Comparative Examples 1-3 increased significantly. Since the oxidation starting temperature of the copper particles in the Comparative Examples is lower than the baking temperature, it is not difficult to understand that most of the copper particles in the Comparative Examples have been oxidized. Among them, under the same conditions, the oxygen content of Example 7 increased by only 0.013, while the oxygen content of Comparative Example 2 increased by 0.735%, and the increase in oxygen content of Example 7 was much lower than that of Comparative Example 2; under the same conditions, the oxygen content of Example 8 increased by only 0.02%, while the oxygen content of Comparative Example 1 increased by 1.658%, and the increase in oxygen content of Example 8 was much lower than that of Comparative Example 1.
[0099] The burnout rates of the composite copper powders of Examples 1 to 16 and Comparative Examples 1 to 3 were tested by thermogravimetric method. Specifically, the composite copper powders were burned to 700° C. in a muffle furnace under a nitrogen atmosphere, and weighed immediately after cooling. The difference in mass before and after burning was divided by the mass before burning to obtain the burnout rate. The results are shown in Table 4.
[0100] Table 4
[0101]
[0102]
[0103] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0104] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A composite copper powder, characterized in that: include: Copper particles; as well as A polysulfur compound attached to the surface of the copper particles, wherein the polysulfur compound is selected from at least one of the compounds represented by formula I, formula II, formula III and formula IV; wherein A1, A2, A3, A4, A5 are each independently selected from S, C=S, C or C-SH groups, and at least two of A1, A2, A3, A4 and A5 are each independently selected from S, C=S or C-SH groups; X1, X2, X3, X4, X5, X6 are each independently selected from S, C=S, C or C-SH groups, and at least two of X1, X2, X3, X4, X5 and X6 are each independently selected from S, C=S or C-SH groups; B1, B2, B3, B 4. B5, B6, and B7 are each independently selected from S, C=S, C, or C-SH groups, and at least two of B1, B2, B3, B4, B5, B6, and B7 are each independently selected from S, C=S, or C-SH groups; L1, L2, L3, L4, L5, L6, L7, and L8 are each independently selected from S, C=S, C, or C-SH groups, and at least two of L1, L2, L3, L4, L5, L6, L7, and L8 are each independently selected from S, C=S, or C-SH groups; A1, A2, A3, A4, A5 may be optionally and independently substituted by R1, X1, X2, X3, X4, X5, X6 may be optionally and independently substituted by R2, B1, B2, B3, B4, B5, B6, B7 may be optionally and independently substituted by R3, L1, L2, L3, L4, L5, L6, L7, L8 may be optionally and independently substituted by R4, and R1, R2, R3, R4 are each independently selected from H, substituted or unsubstituted alkyl having 1 to 25 carbon atoms, substituted or unsubstituted alkenyl having 1 to 20 carbon atoms, substituted or unsubstituted alkynyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 carbon atoms, substituted or unsubstituted aryl having 6 to 20 carbon atoms, and substituted or unsubstituted aralkyl having 7 to 20 carbon atoms.
2. The composite copper powder according to claim 1, characterized in that R1, R2, R3, and R4 are each independently selected from a substituted or unsubstituted alkyl group having 1 to 20 carbon atoms, a substituted or unsubstituted alkenyl group having 1 to 15 carbon atoms, a substituted or unsubstituted alkynyl group having 1 to 10 carbon atoms, a substituted or unsubstituted cycloalkyl group having 3 to 15 carbon atoms, a substituted or unsubstituted aryl group having 6 to 15 carbon atoms, and a substituted or unsubstituted aralkyl group having 7 to 15 carbon atoms.
3. The composite copper powder according to claim 1, characterized in that The substituents on R1, R2, R3 and R4 are each independently selected from H, an alkyl group having 1 to 10 carbon atoms, an alkenyl group having 1 to 10 carbon atoms, an alkynyl group having 1 to 10 carbon atoms, a cycloalkyl group having 3 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms.
4. The composite copper powder according to claim 1, characterized in that The polysulfur compound is selected from at least one of the following compounds, wherein -C4H9, -C 12 H 25 , -C 15 H 31 , -C 19 H 39 All are straight chain alkyl groups:
5. The composite copper powder according to any one of claims 1 to 4, characterized in that: Based on the total mass of the composite copper powder being 100%, the mass of the polysulfide compound attached to the surface of the copper particles is 0.01-0.5%.
6. The composite copper powder according to any one of claims 1 to 4, characterized in that: The burn-out rate of the composite copper powder when burned to 700° C. is 0.01-0.5%.
7. The composite copper powder according to any one of claims 1 to 4, characterized in that: The thermal oxidation starting temperature of the composite copper powder is greater than 250°C.
8. The composite copper powder according to any one of claims 1 to 4, characterized in that: The copper particles are flaky copper particles and / or spherical copper particles. The D50 particle size of the flaky copper particles is 1 to 50 μm; the D50 particle size of the spherical copper particles is 10 to 1000 nm.
9. A method for preparing the composite copper powder according to any one of claims 1 to 8, characterized in that: include: (1) pre-treating the copper particles to remove foreign matter on the surface of the copper particles; (2) preparing a polysulfide compound solution; (3) mixing the pretreated copper particles with the polysulfide compound solution, stirring and / or ultrasonically treating, washing, and drying to obtain composite copper powder.
10. The method according to claim 9, characterized in that In step (1), the copper particles are pretreated with an acid solution; And / or, in step (2), the mass concentration of the polysulfide compound solution is 1 to 20%; And / or, in step (3), mixing, stirring or ultrasonic treatment is carried out at 20 to 80° C., and the stirring or ultrasonic treatment time is 30 to 600 min.
11. A conductive paste, characterized in that: The invention comprises the composite copper powder according to any one of claims 1 to 8 or the composite copper powder prepared by the method according to claim 9 or 10.
12. An electrode, characterized in that: A conductive paste according to claim 11.
13. A solar cell, characterized in that: A method of manufacturing the present invention comprising: providing an electrode as claimed in claim 12.